Zooming in on accretion: I. The structure of halo gas - Nelson, Dylan; Springel, Volker (Arxiv, 2015)
We study the properties of gas in and around 10^12 solar mass halos at z=2 using a suite of high-resolution cosmological hydrodynamic 'zoom' simulations. We quantify the thermal and dynamical structure of these gaseous reservoirs in terms of their mean radial distributions and angular variability along different sightlines. With each halo simulated at three levels of increasing resolution, the highest reaching a baryon mass resolution of ~10,000 solar masses, we study the interaction of filamentary inflow and the quasi-static hot halo atmosphere. We highlight the discrepancy between the spatial resolution available in the halo gas as opposed to within the galaxy itself, and find that stream morphologies become increasingly complex at higher resolution, with large coherent flows revealing density and temperature structure at progressively smaller scales. Moreover, multiple gas components co-exist at the same radius within the halo, making radially averaged analyses misleading. This is particularly true where the hot, quasi-static, high entropy halo atmosphere interacts with cold, rapidly inflowing, low entropy accretion. We investigate the process of gas virialization and identify different regimes for the heating of gas as it accretes from the intergalactic medium. Haloes at this mass have a well-defined virial shock, associated with a sharp jump in temperature and entropy at ~1.25 r_vir. The presence, radius, and radial width of this boundary feature, however, vary not only from halo to halo, but also as a function of angular direction, covering roughly ~85% of the 4pi sphere. Our findings are relevant for the proper interpretation of observations pertaining to the circumgalactic medium, including evidence for large amounts of cold gas surrounding massive haloes at intermediate redshifts.
Gesehen am 06.11.2017